Aphrodisiac Activity of Clove Leaves (Syzygium aromaticum L.) Ethanol Extract and Fractions in Wistar rats - Yanuarty, Rezky; Tuldjanah, Muthmainnah; Wulandari, Ayu (Sciences of Phytochemistry, 2024)
Erectile dysfunction (ED) and premature ejaculation are prevalent male sexual dysfunctions affecting various age groups. This study explores the potential aphrodisiac effects of Clove leaves (Syzygium aromaticum L.), a plant rich in secondary metabolites, including alkaloids, flavonoids, saponins, and steroids. Fractionation of the ethanol extract yielded n-hexane, ethyl acetate, and water fractions. Phytochemical screening revealed the presence of alkaloids, flavonoids, and saponins in the water fraction, while steroids were detected in the ethanol extract, ethyl acetate, and n-hexane fractions. In vivo tests on male rats demonstrated that the ethanol extract, n-hexane, and ethyl acetate fractions significantly reduced mounting latency (ML), increased mounting frequency (MF), and accelerated intromission latency (IL), indicating heightened sexual arousal and endurance. Moreover, these fractions delayed ejaculatory latency (EL) and increased ejaculation frequency (EF), akin to the positive control, X-Gra. Notably, the n-hexane fraction showed the closest efficacy to X-Gra. The presence of steroids in the active fractions suggests their role in eliciting aphrodisiac effects. Further isolation and purification of the active compound(s) may optimize therapeutic outcomes. This study underscores the potential of Clove leaf fractions as natural aphrodisiacs, warranting further investigation for clinical applications.